The Importance of Implementing Divine Values in Elementary Schools - Wan Fahrina Salmi (International Journal of Students Education, 2024)
The purpose of divine values is awareness and is designed to help students understand and the importance of religion in their lives, as well as help them accept that religion. The purpose of this research is qualitative analysis of phenomena using case study research. The aim is to produce work quality students and can be applied in everyday life in the classroom. The research data collection method was carried out using semi- structured interviews, unstructured observation, documentation, and systematic analysis of results. The data analysis method uses the ISI analysis paradigm with data reduction, data presentation from data validation (drawing conclusions). The results of this research show that the forms of morals that exist at SDN Baban 1 Sumenep are as follows: divine values, namely congregational prayer, reading prayers, reading short letters from the Koran, polite values, 3S (smile, greeting, greeting), Siratulahim values, discipline values and social values of society. Sharia values consist of the application of divine values through habituation at the Baban 1 Sumenep elementary school including daily activities, volunteer activities, conditioning, including example.